Irregular sleep/wake patterns in student-athletes exposed to early morning training - Wilson, S. M. B.; Jones, M. I.; Draper, S. B.; Parker, J. K. (Journal of Sports Sciences, 2025)
This study aimed to examine the sleep parameters and sleep/wake regularity of a cohort of student-athletes who start training between 06:30 and 07:00. Twenty-one male Rugby Union players, aged 21 ± 2 years and competing at a national level, were assessed using actigraphy over two weeks, and the Athlete Sleep Screening Questionnaire (ASSQ). Sleep/wake regularity was calculated using the Sleep Regularity Index (SRI). Wilcoxon signed-rank tests showed that nocturnal sleep preceding morning training had a significantly shorter sleep duration (1.8 hr, r = .67), and advanced sleep onset (0.9 hr, r = .50) and sleep offset times (3.2 hr, r = .85) compared to nocturnal sleep preceding free days. The variability of training demands resulted in an inconsistent sleep pattern between consecutive days, resulting in a median SRI score of 67.0 (interquartile range: 17.0). Pearson correlations revealed that lower SRI was significantly associated with a higher daily sleep duration including naps (r = -.62), delayed sleep onset (r = -.50) and sleep offset (r = -.60), and a later chronotype assessed using the ASSQ (r = .52). These findings indicate that early morning training is a factor contributing to irregular sleep/wake patterns in student-athletes, and where feasible should be scheduled at an alternative time.